Profound postinduction hypotension precipitated by immune checkpoint inhibitors: a case report - Lu Che; Afang Zhu; Wen Chen; Chunhua Yu (Journal of Medical Case Reports, 2024)
Abstract Background With the increasing use of immune checkpoint inhibitors (ICIs) in cancer therapy, perioperative healthcare professionals need to be vigilant about potential immune-related adverse events (irAEs). We report a case of severe postinduction hypotension in a patient undergoing laparotomy due to suspected intraabdominal bleeding from gastric cancer and Krukenberg tumors, caused by unrecognized hypothyroidism precipitated by ICIs. Case presentation A 65-year-old Chinese female with a history of gastric adenocarcinoma and Krukenberg tumors, previously treated with nivolumab, presented to the emergency room with abdominal pain and hypotension. Despite ruling out other causes, including hypovolemia and anaphylaxis, her hypotension persisted. The patient was found to have severe hypothyroidism, likely an irAE from the use of nivolumab. Thyroxine replacement therapy resolved the hypotension, and the patient recovered uneventfully after surgery. Conclusions This case underscores the importance of considering irAEs, such as hypothyroidism, in patients treated with ICIs. Perioperative healthcare providers must remain vigilant for potential complications and promptly recognize and manage irAEs to optimize patient outcomes.